Analysys Of The Influence Of Service Quality And Customer Satisfaction At Customer Loyalty And Corporate Image In Tge Company It Service Delivery Pt Xyz - Fahmirakhman Abdullah, Reyhan; Apsari Sugiat, Maria (Publisher Cv. Inara, 2025)
This research explores a number of factors that contribute to customer loyalty and corporate image in the context of IT services. Regression analysis was used to evaluate the relationship between the variables of service quality and customer satisfaction with customer loyalty and corporate image. This research provides important implications for the management of PT XYZ in improving service quality and customer satisfaction to strengthen customer loyalty and improve the company's image. Therefore, recommendations are given to improve service strategies and customer relationship management to maintain and increase customer loyalty and improve the company's image in the IT service industry.